Novas formas cristalinas do fármaco anti-HIV lamivudina com ácidos 1,2-dicarboxílicos: preparação, caracterização e solubilidade - Silva, Cameron Capeletti da (2014)
Co-crystallization of active pharmaceutical ingredients has been widely studied lately in order to improve the solid state features of such compounds, for example solubility, and also to protect the intellectual property of such compounds. Multicomponent molecular crystals can be prepared from both supramolecular synthon and screening approaches, which involve the variation of crystallization conditions. In this way, molecular crystal engineering is a strategy to improve solid state properties of drugs related to their efficacies. One branch of the lamivudine crystal engineering deals with its protonable pyrimidine-based nitrogen being a recipe of crystallization with carboxylic acids. Such strategy has yielded several pharmaceutical co-crystals and salts of APIs that have lamivudine-like heterocyclic nitrogens by choosing suitable carboxylic acids as a salt/co-crystal former. In this context and in relation to the drug antiretroviral nucleoside reverse transcriptase inhibitor lamivudine, four new crystalline phases thereof were prepared, their crystal structures were determined by X-ray diffraction by single crystal, and their solubility in water were measured. For the first time it was observed an in-plane pairing of lamivudine with the carboxylate and carboxyl functionalities of a same salt former unit giving rise to a trimer and a tetramer in the structures of lamivudine hydrogen phthalate hemihydrate and lamivudine hydrogen 4,5-dichlorophthalate, respectively. Besides, a new synthon have been found in the first salt. All lamivudine salts were less soluble than the lamivudine form II (free base). The unexpected heterosynthon can be related to the slightly higher solubility of lamivudine hydrogen 4,5-dichlorophthalate when compared to the other salts prepared in this study.